THE BETRAYAL IN THE FILM, MALEFICENT BY ROBERT STROMBERG: FEMINISM APPROACH - Yani, Pinka; Ningsih, Ayu Melati (Fakultas Sastra UMN AL Washliyah, 2024)
This research aims to find out the types of betrayal and the impact of betrayal committed by Stefan character against Maleficent and Aurora through the Feminism approach. This research uses qualitative method with descriptive approach. The data used is Maleficent 2014 movie by Robert Stomberg. In this research, the analysis is also conducted using Radical Feminism theory to find out how the action reflects the dynamics of patriarchal power and exploitation of women depicted in Maleficent. The results show that the form of betrayal of Stefan consists of 4 types, namely lying, pretending to love, breaking promises, and breaking trust and the impact of betrayal is 6, namely anger, sadness, hatred, depression, irritation, and emotional. This study found that in the context of Betrayal and Feminism in the movie